Developing a scale for assessing coping behavior in situations of danger - N. V. Rodina; O. Iu. Dotsenko; A. V. Kernas; L. P. Pereviazko; L. K. Vornikova (Ukrainian Society of Ophthalmologists, 2022)
Background: The paper is focused on developing a psychodiagnostic tool for assessing coping behavior in situations of danger. Studies of coping behavior became increasingly important with the beginning of the Russian invasion in Ukraine on February 24, 2022. The version developed may become a reliable auxiliary tool for assessing the adaptive capacity of the personality, which is believed to be promising and of increasing importance for further studies. Purpose: To develop a psychodiagnostic tool for assessing coping behavior in danger situations to improve the adaptive capacity of the personality. Material and Methods: The study sample was composed of 311 responders (165 men and 146 women; mean age, 33.7 years). The study was conducted with the use of the seven-factor model of the Ways of Coping Questionnaire (WOCQ) as modified by Rodina. R-Studio software (version 1.4.1717) was used for statistical analyses of the questionnaire which included exploratory and confirmatory factor analysis, structural equation modeling, scale reliability analysis, correlation analysis and descriptive statistic analysis. Results: The Ukrainian-language five-factor model of the Scale for Assessing Coping Behavior in Situations of Danger developed includes the following subscales: Acceptance and Passive Reliance on Support, Acceptance and Passive Pessimism, Acceptance and Passive Optimism, Acceptance and Active Fighting, and Non-Acceptance and Dissociation. Application of the method for assessing coping behavior in situations of danger is promising and of increasing importance for further studies in order to improve the adaptive capacity of the personality.